Design and development of a qualitative simulator for Learning organic reactions - Tang, Y.C.A.; Rahman, N.A.; Zain, Sharifuddin Md (Kluwer (now part of Springer), 2009)
Our work features an ontology-supported framework for developing a qualitative simulator for explaining the behaviors of selected sample of organic chemistry reactions. The design of the simulator uses Qualitative Reasoning (QR), and in particular, Qualitative Process Theory (QPT) for constructing qualitative models and the simulation of basic steps in the chemical reactions such as creating and deleting bonds. The qualitative simulator allows learners to access notions of how the behavior of chemical systems evolves in time. Students would benefit from it in terms of improving their reasoning skills and enhancing their understanding in organic processes. The roles of each functional component of the qualitative simulator will first be introduced. Then, we move on to discuss the qualitative modeling and simulation design for reproducing the chemical behaviors of organic reactions. Finally, a discussion on the simulation results and explanation generation capability are presented.